Mello and Campos (1974) method adapted for the recovery of cestodes in birds ( Gallus domesticus ) - Silva,Giane Serafim da (2016)
ABSTRACT: The specific diagnosis and evaluation of the intensity of avian helminth infections are essential for efficacy studies and the determination of drug doses targeted to their control. This study evaluated the Mello and Campos method, originally described for parasitological diagnosis in dogs, in the recovery of scolices from cestode parasites of poultry (Gallus domesticus ). A total of 52 naturally infected birds obtained from farms underwent parasitological necropsy using the Mello and Campos method. The method consisted of four steps: content, soaking, scraping and evaluation. The number of scolices recovered per bird ranged from 1 to 4,345, and the highest number of scolices was recovered from material derived from the soaking step. The cestodes species diagnosed were Amoebotaenia cuneata , Choanotaenia infundibulum , Hymenolepis sp., Raillietina tetragona , Raillietina echinobothrida and Raillietina cesticillus . The Mello and Campos method, originally used to test for helminths in dogs, was effective in avian cestode testing because it includes a soaking step, which enables a more efficient recovery of scolices.